Social Media Dynamics: Interpersonal Trust and Self-Disclosure on Instagram Second Accounts - Iloen, Alice Sinta Natalia; Kusumiati, Ratriana Yuliastuti Endang (Guidance and Counseling Study Program, Pattimura University, 2024)
In the digital age, technology and the internet have become integral to daily life in Indonesia. With 210 million Indonesians connected to the internet in 2021-2022, social media is a dominant activity, especially among those aged 19-34. This study examines the relationship between interpersonal trust and self-disclosure among Instagram second account users in Palangka Raya. Utilizing a quantitative correlational design, 130 participants were surveyed using adapted scales for interpersonal trust and self-disclosure. Descriptive statistics showed medium levels of both interpersonal trust (mean = 52.71) and self-disclosure (mean = 45.72). Spearman's correlation analysis revealed a significant positive relationship (r = 0.308, p < 0.01), indicating that higher trust levels are associated with greater self-disclosure. These findings underscore the importance of trust in fostering open communication on social media. The study contributes to understanding the dynamics of trust and self-disclosure in early adulthood but highlights the need for further research with more diverse samples to explore additional influencing factors.